Research on bar deflection of low-stress cropping process under bending-shear coupling effect. (December 2022) - Zhang, Lijun; Fu, Shulin; Yang, Ning; Yang, Bohan; Zhang, Qiang; Tao, Jishao; Wang, Hang; Xu, Jiayi; Zhao, Qing; He, Qingqiang; Zhang, Xiaodong
Graphical abstract: Highlights: Stiffness equivalent transformation method for cropping bar is proposed. Bar deflection formula under bending-shear coupling effect is established. The real-time synchronous dynamic bar deflection test platform is built. The rationality of bar deflection formula is verified by experiment results. Evaluation parameter quantifying the contact form of loading die-bar is proposed. Abstract: In view of the influence of shear effect on bar deflection in low-stress cropping, which makes it difficult to control the loading die and seriously affects the surface quality of cropping bar, based on the energy balance theory in this paper, the stiffness equivalent transformation of the bar with annular V-shaped notch and dynamic crack is carried out, and the coupling effect of bending moment and shear force on the bar deflection before and after crack initiation is quantified. Based on it, the deflection characterization formula for the whole cropping process of the bar with different length-diameter ( L/ 2 R ) ratios is established. The change laws of bar deflection with different L/ 2 R ratios are analyzed by XFEM method. Especially for the bar with L/ 2 R  ≤ 2.84, it is pointed out that it is necessary to consider the influence of shear deflection on the basis of bending deflection, and its influence degree decreases with the increase of L/ 2 R . The real-time synchronous dynamic deflection test platform is built on the cropping machine of rotary bending. The research shows that the calculated values obtained by the deflection characterization formula proposed are in good agreement with the corresponding experimental results. The evaluation parameter, maximum contact stress reduction ratio ξ ( p-l )/ p, is proposed to characterize the degree of surface contact stress reduction under line contact loading relative to point contact loading. It is pointed out that the variation range of ξ ( p-l )/ p of the bar with different L/ 2 R ratios under the influence of deflection is as high as 49.8%-64.1%. And further application of double bearings outer ring loading is also beneficial to obtain high cropping quality.